SOSIALISASI SANITASI DAN HIGIENIS KERUPUK KULIT PADA IKM RIZKY DI KOTA PADANG - Indri Juliyarsi; Sri Melia; Deni Novia; Ade Sukma; Tuty Anggraini; Najmiatul Fitria (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
The skin crackers are well-known and favored as regional superior products which are very potential to be developed. The purpose of this service is to improve sanitation and hygiene aspects, where the layout of production in accordance with SSOP and GMP. Approach methods offered to support knowledge programs using trained and consultation with the methods used are lectures and discussions. The focus of activities is the renovation of layout of production space and sanitation equipment. Based on the service of introducing appropriate technology, Mitra is very enthusiastic about using cleaning tools for wet and clean production spaces with sanitary and hygienic and storage space equipped with container boxes so that it can increase the shelf life of the skin after drying, as well as improve the production space so that the production is running well in accordance with SSOP, GMP in production.